The concept of jinn in Islam and Christian orthodox ( comparative study of the books of Abbot N. and Malik Ibrahim ) - Vdovin Ilya Mikhailovich (Program Pasca Sarjana UIN Sunan Kalijaga, 2015)
wt,1/nr,c.1